A dynamic risk management approach to reduce harm in hypertrophic cardiomyopathy. (June 2018) - Friedberg, Mark K.; Barach, Paul
Abstract: Hypertrophic cardiomyopathy (HCM) is thought to be a leading cause of sudden cardiac death (SCD) in athletes, and while SCD is the most dramatic and feared of all HCM presentations, its exact incidence remains unclear. Current expert opinion and consensus panels that formulated exercise recommendations in HCM to reduce the risk of sudden death by avoiding competitive sport are based on scant, observational, often circumstantial, and sometimes conflicting evidence. These recommendations rely on multiple cross-referencing of few original papers from a limited number of research groups. At the same time, there is accumulating data that recommendations to avoid competitive exercise in HCM come at the price of avoidance of all physical activity which carries its own risks and complications. Consequently, physicians are challenged when asked by concerned parents and children to justify overly restrictive clinical judgements and guidance about permitted exercise levels in HCM. In this manuscript, we review the strength of the evidence underlying current sport recommendations in HCM. We propose that developing a working risk management approach to assist anxious parents and children is imperative and must be customized to the needs of the child and their parents. Rather than a blanket recommendation to avoid competitive sport, we believe that HCM patients deserve to have a robust and real-world risk assessment strategy that is tailored to the individual needs, discussed with the child and their parents, and updated as the child grows and matures. Highlights: Hypertrophic cardiomyopathy (HCM) is considered a major cause of sudden cardiac death (SCD); but the incidence is unclear. Current expert recommendations to avoid competitive sport are based on scant, observational, often circumstantial evidence. Recommendations to avoid competitive exercise often leads to avoidance of all physical activity which carries its own risks. Physicians are challenged when asked by concerned families to justify guidance about permitted exercise levels in HCM. We propose that a working risk management approach to assist the child and parents should be customized to their needs. Patients deserve a real-world risk assessment strategy tailored to individual needs, discussed with them and updated over time.